Diseño de un sistema para la evaluación de biocombustibles líquidos en la producción de vapor en la caldera del laboratorio de transferencia de calor II (2018)
The project began with a plan of the steam production system of the heat transfer laboratory II to have a more detailed view of how the system works and how it is involved with the other equipment of the facility, in order to trace the limits of the system that will be studied in this project. Throughout the development of the plans was characterized the steam production system of the laboratory where we find different equipment and instruments used for the boiler and its burner to operate satisfactorily, these elements such as pressure gauges, thermometers, level indicators, among others . They will be useful to specify the mass and energy balances of both units by means of a quantification of variables.